Prospective, multicenter study of P4HB (Phasix™) mesh for hernia repair in cohort at risk for complications: 3-Year follow-up. (January 2021) - Roth, John Scott; Anthone, Gary J.; Selzer, Don J.; Poulose, Benjamin K.; Pierce, Richard A.; Bittner, James G.; Hope, William W.; Dunn, Raymond M.; Martindale, Robert G.; Goldblatt, Matthew I.; Earle, David B.; Romanelli, John R.; et al.
Abstract: Background: This study represents a prospective, multicenter, open-label study to assess the safety, performance, and outcomes of poly-4-hydroxybutyrate (P4HB, Phasix™) mesh for primary ventral, primary incisional, or multiply-recurrent hernia in subjects at risk for complications. This study reports 3-year clinical outcomes. Materials and methods: P4HB mesh was implanted in 121 patients via retrorectus or onlay technique. Physical exam and/or quality of life surveys were completed at 1, 3, 6, 12, 18, 24, and 36 months, with 5-year (60-month) follow-up ongoing. Results: A total of n = 121 patients were implanted with P4HB mesh (n = 75 (62%) female) with a mean age of 54.7 ± 12.0 years and mean BMI of 32.2 ± 4.5 kg/m 2 (±standard deviation). Comorbidities included: obesity (78.5%), active smokers (23.1%), COPD (28.1%), diabetes mellitus (33.1%), immunosuppression (8.3%), coronary artery disease (21.5%), chronic corticosteroid use (5.0%), hypo-albuminemia (2.5%), advanced age (5.0%), and renal insufficiency (0.8%). Hernias were repaired via retrorectus (n = 45, 37.2% with myofascial release (MR) or n = 43, 35.5% without MR), onlay (n = 8, 6.6% with MR or n = 24, 19.8% without MR), or not reported (n = 1, 0.8%). 82 patients (67.8%) completed 36-month follow-up. 17 patients (17.9% ± 0.4%) experienced hernia recurrence at 3 years, with n = 9 in the retrorectus group and n = 8 in the onlay group. SSI (n = 11) occurred in 9.3% ± 0.03% of patients. Conclusions: Long-term outcomes following ventral hernia repair with P4HB mesh demonstrate low recurrence rates at 3-year (36-month) postoperative time frame with no patients developing late mesh complications or requiring mesh removal. 5-year (60-month) follow-up is ongoing. Highlights: Prospective, multicenter, open-label study of safety, performance, and outcomes. Poly-4-hydroxybutyrate mesh implanted in n = 121 patients via retrorectus or onlay. 82 patients (67.8%) completed 36-month follow-up. Hernia recurrence (n = 17, 17.9% ± 0.4%) and SSI (n = 11, 9.3% ± 0.03%) at 3 years. No patients developed late mesh complications or required mesh removal.